Community Empowerment to Reduce Extreme Poverty in Garut Regency Through Business Incubators - Gumilar, Budi Gan Gan Gumilar; Kania, Ikeu; Mulyaningsih (Ilomata International Journal of Social Science, 2025)
Extreme poverty remains a persistent challenge in Indonesia, with approximately 2.5% of the population living on less than $2.15 per day (World Bank, 2023). This condition is not solely economic but also deeply intertwined with social and cultural dimensions, limiting access to education, healthcare, and employment opportunities. This study examines the impact of business incubators on reducing extreme poverty in Garut Regency by analyzing changes in income and managerial knowledge using paired t-tests. The findings indicate a significant increase in income, with an average growth of 35% (p-value = 0.000), alongside a notable improvement in managerial knowledge (p-value = 0.001) following participation in the incubator program. These results underscore the effectiveness of business incubators in enhancing both financial stability and entrepreneurial capacity. However, critical challenges remain, particularly regarding access to capital and heightened market competition, which disproportionately affect entrepreneurs in remote areas. To address these barriers and ensure the long-term sustainability of incubator initiatives, stronger collaboration among local governments, financial institutions, and the private sector is essential. Such partnerships can facilitate targeted financial support and broader market access. Overall, this research affirms the role of business incubators as a strategic tool for community empowerment and poverty alleviation, while emphasizing the need for ongoing support mechanisms and policy innovation to foster resilient, inclusive economic development in disadvantaged regions such as Garut Regency.